2003
DOI: 10.1086/378275
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Aspiration-Injection-Reaspiration Drainage Plus Albendazole or Mebendazole for Hepatic Cystic Echinococcosis: A Meta-analysis

Abstract: Using meta-analysis methodology, we compared the clinical outcomes for 769 patients with hepatic cystic echinococcosis treated with percutaneous aspiration-injection-reaspiration (PAIR) plus albendazole or mebendazole (group 1) with 952 era-matched historical control subjects undergoing surgical intervention (group 2). The rate of clinical and parasitologic cure (P<.0001) was greater in patients receiving PAIR plus chemotherapy. Disease recurrence (P<.0001), major complications (anaphylaxis, biliary fistula, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
153
0
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(164 citation statements)
references
References 40 publications
4
153
0
7
Order By: Relevance
“…Our results, however, are consistent with other reports of PT. 17,22,[31][32][33][34] In our study, both the groups showed a pattern of rise in titres on IgG ELISA 1 month after the intervention, followed by a gradual fall to baseline values. The rise in titres after either intervention reflects an increase in IgG antibody that occurs owing to small amounts of echinococcal antigens gaining access to the blood stream during the procedure.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Our results, however, are consistent with other reports of PT. 17,22,[31][32][33][34] In our study, both the groups showed a pattern of rise in titres on IgG ELISA 1 month after the intervention, followed by a gradual fall to baseline values. The rise in titres after either intervention reflects an increase in IgG antibody that occurs owing to small amounts of echinococcal antigens gaining access to the blood stream during the procedure.…”
Section: Discussionmentioning
confidence: 79%
“…[19][20][21] A meta-analysis of multiple studies on treatment of CE showed a cure rate of 89.8% for patients undergoing surgery. 22 Considering a 10% difference in cure rates to be clinically important, 44 patients are required to be 90% sure that the upper limit of a one-sided 95% confidence interval (CI) (or equivalently a 90% two-sided CI) will exclude a difference in favour of the standard group of .10%. A sample size of 44 patients was therefore selected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique was first developed by Mueller et al as an alternative treatment method against surgical excision of the liver hydatid cysts [7]. Although, puncture of a hydatid cyst has long been discouraged because of potential complications, such as anaphylactic shock or risk of iatrogenic spreading, there is an expanding literature suggesting that PAIR is effective for treatment of primary uncomplicated hepatic cysts [13]. However, this technique has been used for solid organ hydatid cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, first treatment choice of muscular hydatid cyst is the combination of en bloc resection and albendazole chemotherapy [2]. On the other hand, puncture, aspiration, injection of scolicidal agent and reaspiration (PAIR) is a non-operative technique which is now widely used for the treatment of liver hydatid cyst [13]. We report a case of primary hydatid cyst seated in erector spinae muscle which was treated successfully with PAIR technique.…”
Section: Introductionmentioning
confidence: 99%